The Predictors of the Likelihood of Contracting HIV/AIDS Among Kenyan Women and the Role of Tertiary Home Economics Programs in the Prevention of the Pandemic - Muchee, Tabitha M. (Journal of the Philippine Association for Technology in Home Economics in State Colleges and Universities, Inc., 2004)
This study was conducted to determine the predictors of the likelihood of contacting HIV/AIDS among Kenyan women and to come up with a Tertiary Home Economic Program in the prevention of the pandemic. A total of 350 women; 265 non-HIV and 85 HIV positive, served as the respondents. A total of 11 (five administrators and six Home Economics teachers) participated in the Focus Group Discussions. The statistic tools used for data gathering were percentages, standard deviation, mean, t-test and regression. Results showed that majority of the respondents were single, religious, social, and were brought up in democratic families. The significant difference between non-HIV and HIV positive was found in terms of age, educational background, personality type, hobbies, residence, family income, parents occupation and education, family discipline; knowledge and attitude. However, there was no significant difference in terms of religion and sexual behavior. The predictors of the likelihood of contacting HIV/AIDS included; religiosity, forced sex, media influence, residence, educational attainment, and family discipline. Tertiary Home Economics should incorporate HIV/AIDS prevention in its curriculum to promote family well-being.